ISOLATION AND CHARACTERIZATION OF β-SITOSTEROL FROM ACANTHOSTRONGYLOPHORA INGENS SPONGE AND ITS ANTICANCER ACTIVITY USING AN IN SILICO APPROACH - Ajuk Sapar; Riska Mardiyanti; Nur Asmi; Nunuk Hariani Soekamto; Millenia Millenia; Nurmasyita Nurmasyita; Nurmalah Syam (Walisongo Journal of Chemistry, 2026)
This study reports the isolation of β-sitosterol from the methanol extract of the sponge Acanthostrongylophora ingens, collected from the Spermonde Islands. The methods employed in this study included extraction, phytochemical testing, toxicity assessment, and chromatographic fractionation. Characterization of the isolate was performed using FTIR and GC-MS techniques. Isolate I-3 showed characteristic absorption bands corresponding to functional groups associated with β-sitosterol, and its molecular mass was confirmed at 414 g/mol. The potential anticancer activity was evaluated using an in silico approach. The toxicity test results indicated that the methanol extract exhibited high toxicity, with an LC₅₀ value of 24.831 µg/mL. Furthermore, the in silico molecular docking analysis d emonstrated a strong interaction between β-sitosterol and the target protein, with the lowest binding energy recorded at −11.49 kcal/mol. This significant value suggests that β-sitosterol has excellent interaction potential with the active site of the target protein, highlighting its promising candidacy as an anticancer agent.